Comparison of external fixation and intramedullary nailing in geriatric patients with intertrochanteric fractures of the femur - Adanaş, Cihan; Özkan, Sezai (Journal of Surgery and Medicine, 2019)
Aim: The healing time of femoral intertrochanteric fractures in the elderly population is prolonged due to the presence of osteoporosis. However, mortality is high because of major causes such as embolism due to long-term bed rest. It is particularly important that these patients be operated and given the freedom to move in the early postoperative period. In this study, we aimed to compare the clinical outcomes of Proximal Femoral Nail (PFN) and External Fixation (EF) in older patients with intertrochanteric fractures of the femur (ITFF). Methods: This study included 72 patients aged 65 years or older who were diagnosed with ITFF and underwent PFN (n=38) or EF (n=34) between 2011 and 2017. Patient data including demographic characteristics, preoperative ASA score, surgical technique, postoperative complications, and functional outcomes at final follow-up, Harris Hip Score (HHS) and Mean Mobility Score (MMS) scores were recorded for each patient. Results: The results indicated that both PFN and EF provided equally satisfactory functional outcomes in the patients. EF was found to have major advantages including significantly lower operative times, lower intraoperative blood loss, and administration of sedation only in high-risk patients. PFN was also found to have remarkable advantages such as lower reoperation risk, reduced mortality, and lower risk of superficial wound infection. Conclusion: Although both PFN and EF were found to have remarkable advantages, PFN seems to be more advantageous in terms of complications. Meaningfully, PFN could be more reliable and effective in the treatment of extracapsular ITFF in old-age patients.